1998
DOI: 10.1038/sj.bjp.0702103
|View full text |Cite
|
Sign up to set email alerts
|

EB1089, a synthetic analogue of vitamin D, induces apoptosis in breast cancer cells in vivo and in vitro

Abstract: 1 E ects of the synthetic vitamin D analogue EB1089 on indices of apoptosis in cultured human breast cancer cells and in nitrosomethylurea-induced rat mammary tumours in vivo were investigated. 2 At a dose of 0.5 mg kg 71 body weight, EB1089 caused signi®cant inhibition of tumour progression over the 28 day treatment period in the absence of a signi®cant increase in serum calcium concentration. Higher doses of EB1089 (1 and 2.5 mg kg 71 ) produced substantial regression of the experimental tumours which was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 47 publications
2
43
0
1
Order By: Relevance
“…This is an interesting observation as the cells do express VDR (Kawa et al, 1996 and unpublished data) and are clearly responsive to the analogues, which have been shown to induce apoptosis in various other cell types (James et al, 1995(James et al, , 1998Danielsson et al, 1997). Furthermore, EB1089 and CB1093 not only failed to induce apoptosis by themselves, but were also able to completely block Pretreatment with EB1089 for 3 days was shown to be enough to completely block induction of apoptosis by 9cRA.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is an interesting observation as the cells do express VDR (Kawa et al, 1996 and unpublished data) and are clearly responsive to the analogues, which have been shown to induce apoptosis in various other cell types (James et al, 1995(James et al, , 1998Danielsson et al, 1997). Furthermore, EB1089 and CB1093 not only failed to induce apoptosis by themselves, but were also able to completely block Pretreatment with EB1089 for 3 days was shown to be enough to completely block induction of apoptosis by 9cRA.…”
Section: Discussionmentioning
confidence: 67%
“…(Korsmeyer, 1999). For example, in breast cancer cells which undergo apoptosis in response to vitamin D compounds, downregulation of the anti-apoptotic protein Bcl-2 and an increased Bax/Bcl-2 ratio can be observed (James et al, 1998). This is also observed in HL-60 leukaemia cells, and is thought to be a mechanism whereby vitamin D derivatives potentiate induction of apoptosis by 9cRA (James et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Observations that support combining 1,25(OH) 2 D 3 with ionising radiation include the following: (a) both IR and 1,25(OH) 2 D 3 induce apoptosis in prostate carcinoma cells by apparently distinct pathways (Welsh et al, 1995;Billis et al, 1998;James et al, 1998;Pirianov et al, 1999;Ding and Fisher, 2001;McGuire et al, 2001;Sheard, 2001;Liu et al, 2002); (b) other agents that induce cellular differentiation, for example, phenylacetate, platelet-derived growth factor and retinoic acid, are known to enhance the cytotoxic effects of IR (Bill et al, 1992b;Miller et al, 1997;Hoffmann et al, 1999); (c) EB 1089 has been shown to enhance the radiation sensitivity of breast carcinoma cells (Sundaram and Gewirtz, 1999). These findings strongly suggest that 1,25(OH) 2 D 3 may enhance the cytotoxic effects of IR on prostate cancer cells.…”
mentioning
confidence: 99%
“…The synthetic analogue seocalcitol is 50 -200 times more potent than vitamin D in inhibiting growth and inducing differentiation of cancer cell lines Kissmeyer et al, 1997). In vivo studies in animal models have shown that seocalcitol can cause regression of established tumours, prevent the development of metastases, and prolong survival time in tumour-bearing animals (Colston et al, 1992(Colston et al, , 1997James et al, 1998;Lokeshwar et al, 1999;Nickerson and Huynh, 1999), with significant inhibition of tumour progression achieved at doses that do not cause significant hypercalcaemia (Colston et al, 1992). Furthermore, seocalcitol inhibits growth of pancreatic cancer cells in vitro (Zugmaier et al, 1996;Pettersson et al, 2000) and inhibits growth in vivo of pancreatic cancer xenografts in immunodeficient mice (Colston et al, 1997).…”
mentioning
confidence: 99%